THE INFLUENCE OF CLOUD-BASED ENTERPRISE RESOURCE PLANNING (ERP) IMPLEMENTATION ON THE EFFECTIVENESS OF ACCOUNTING INFORMATION SYSTEMS - Fatimah Fatimah; Nur Amalia Ashar; Anggie Wulandari; Surianti Surianti; Rahmat Feri Ismail; Ainul Ainul; Dharul Islamanandad (CV. Adiba Aisha Amira, 2025)
This research aims to examine the impact of implementing cloud-based Enterprise Resource Planning (ERP) systems on the effectiveness of accounting information systems (AIS) through a literature review approach. Cloud ERP is a technological solution that offers cross-functional data integration and real-time access, which has the potential to enhance the efficiency, reliability, and accuracy of accounting information. This study was conducted by reviewing various scientific publications, books, and industry reports published in the last 5 to 10 years. The study results indicate that cloud-based ERP contributes positively to the improvement of operational efficiency, accuracy of financial reporting, and ease of information access that supports strategic decision-making. Features such as transaction automation, audit trails, and module integration in cloud ERP have proven to enhance the quality of information produced by the accounting system. However, the effectiveness of the system is still influenced by factors such as organizational readiness, user training, and implementation suitability.